Հայաստանում կարմրուկի, կարմրախտի համաճարակաբանական հսկողության բնութագիրը վերացման փուլում - Ն. Ս. Մելքոնյան (ՀՀ ԳԱԱ հրատ.)
Целью исследования является оценка качества эпидемиологического надзора за корью и краснухой на стадии их ликвидации. The objective of this research is to assess the quality of epidemiological surveillance of measles and rubella at the stage of their elimination in Armenia.
Keywords: Medicine; Epidemiology